Respostas
respondido por:
0
25 + ( 12 + ( 8 - 5 + 12 )
= 25 + (13 + 15 )
= 25 + ( 28)
= 53
= 25 + (13 + 15 )
= 25 + ( 28)
= 53
respondido por:
0
Olá!!!
Resolução!!
= 25 + ( 12 + ( 8 - 5 + 12 )
= 25 + ( 12 + ( 8 + 7 )
= 25 + ( 12 + 15 )
= 25 + 27
= 52
R = 52
Espero ter ajudado!!!
Resolução!!
= 25 + ( 12 + ( 8 - 5 + 12 )
= 25 + ( 12 + ( 8 + 7 )
= 25 + ( 12 + 15 )
= 25 + 27
= 52
R = 52
Espero ter ajudado!!!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás